The potential of cystatin-C to evaluate the prognosis of acute heart failure: A comparative study. (2nd October 2015) - Kim, Tae-Hun; Kim, Hyungseop; Kim, In-Cheol
Abstract : Background : The prognosis of acute heart failure (HF) can be determined by cardio-renal function which is assessed by cystatin-C (Cys-C). We evaluated whether Cys-C could be a more useful prognostic indicator in acute HF, compared with uric acid (UA) and N-terminal pro-B-type natriuretic peptide (NT-proBNP). Methods : Two hundred thirty-two HF patients in the emergency room were studied using measurements of Cys-C, UA, and NT-proBNP. During the follow-up, cardiac events, defined as the composites of recurrent HF or cardiac death, were determined. Results : Seventy-seven cardiac events (28 cardiac deaths, 49 recurrent HFs) occurred over two years. The events group revealed higher levels of Cys-C, UA, and NT-proBNP. They showed increased blood urea nitrogen and creatinine, reduced septal tissue Doppler velocity (TVI-Sm), and low frequencies of beta-blockers (BB), diuretics and angiotensin-converting enzyme inhibitors/-receptor blockers. Cys-C (the best cutoff: 1.7 mg/l) had a steady, persistent hazard ratio (HR) over two years. On multivariate analysis, Cys-C, TVI-Sm, and BB were significant predictors for adverse events. Cys-C provided an incremental value for prognosis more than NT-proBNP and UA did over the follow-up period. Conclusions : Compared with UA and NT-proBNP, Cys-C could be better prognostic biomarker for cardiac events two years after acute HF.